COVID-19 resulting in bilateral pulmonary emboli and a right ventricular thrombus: association or causation? A case report. Issue 5 (2nd October 2020) - Kaplan, Jason G; Kanwal, Arjun; Malek, Ryan; Dickey, John Q; Keirn, Richard; Zweig, Bryan; Minter, David
Abstract: Background: SARS-CoV-2 is a novel viral illness originating out of Wuhan China in late 2019. This global pandemic has infected nearly 3 million people and accounted for 200 000 deaths worldwide, with those numbers still climbing. Case summary: We present a 54-year-old patient who developed respiratory failure requiring endotracheal intubation from her infection with SARS-CoV-2. This patient was subsequently found to have a right ventricular thrombus and bilateral pulmonary emboli, likely contributing to her respiratory status. On the 14th day of hospitalization, the patient was successfully extubated, and 5 days later was discharged to the rehabilitation unit. Discussion: SARS-CoV-2 presents primarily with pulmonary symptoms; however, many patients, particularly those who are severely ill, exhibit adverse events related to hypercoagulability. The exact mechanism explaining this hypercoagulable state has yet to be elucidated, but these thrombotic events have been linked to the increased inflammation caused by SARS-CoV-2. This novel viral illness is still largely misunderstood, but the hypercoagulable state, seen in severely ill patients, appears to play a major role in disease progression and prognosis.